Development of Instruments for The Feasibility of Instructional Media on General Biology Material - Prayitno, Trio Ageng; Hidayati, Nuril (Universitas Muhammadiyah Surakarta, 2021)
Purpose: produce a valid research instrument to measure the feasibility of instructional media on general biology material. Methodology: This research and development uses the Thiagarajan model, which consists of define, design, and develop. The research subjects were two lecturers out of 10 lecturers in the department of Biology Education at IKIP Budi Utomo. The research instrument is a questionnaire on the validity of the instructional media instrument given to two lecturers. The research data is the instrument validity score and comments from experts. The data analysis technique is descriptive qualitative. Results: The results of the study indicate that the instrument of eligibility for instructional media that has been developed is valid (99.36%, very valid criteria), so that it can be used as a measuring instrument for the validity of instructional media on general biology material. Applications/Originality/Value: In the case of existing development research, researchers often rule out testing the validity of the instrument, meaning that here it is necessary to emphasize that the researcher must first test the validity of the instrument. This is important for researchers in the field of formal education and researchers in the instructional media industry so that the research instruments are unquestionable and the research data obtained can be accounted for. So that the instructional media developed will be effective in overcoming learning problems. Thus, the development of this research instrument could be a valuable guide for researchers to use research instruments that have been declared valid by experts.